The effect of dehydration on wrestling minimum weight assessment - Bartok, C.; Schoeller, D. A.; Clark, R. R.; Sullivan, J (Medicine & Science in Sports & Exercise, 2004)
Given that some wrestlers arrive for minimum weight (MW) testing in a dehydrated condition, it is important to understand the effects of dehydration on MW assessment methods. PURPOSE: To determine the effect of dehydration on the assessment of MW by three-site skinfolds with the Lohman formula (SF), leg-to-leg bioelectrical impedance analysis (BIA), and multifrequency bioelectrical impedance spectroscopy (BIS) compared with a four-component (4C) criterion. METHODS: Twenty-two male collegiate wrestlers (mean +/- SD, age: 19.9 +/- 1.4 yr, height: 174.0 +/- 6.8 cm, body mass: 77.4 +/- 9.1 kg) had their body composition assessed by the 4C criterion, hydrostatic weighing (HW), SF, BIA, and BIS in euhydration (EUH) and dehydration (DEH). Subjects dehydrated 2-5% of body weight through fluid restriction and exercise in a hot environment. RESULTS: In EUH, the total error (TE) for HW (1.75 kg) and SF (2.15 kg) were not significantly different, but the TE for HW and SF methods were significantly lower than the TE for both BIS (3.68 kg) and BIA (3.77 kg). In DEH, SF, BIA, and BIS methods had a TE approaching or exceeding 4 kg (8.8 lb). Dehydration increased the TE for SF and BIA through an artificial lowering of body weight and for BIS by an increased error in intracellular water prediction. CONCLUSION: Acute thermal dehydration violates assumptions necessary for the accurate and precise prediction of MW by SF, leg-to-leg BIA, and multifrequency BIS.